Identifikasi Permasalahan Pengelolaan Sampah di Daerah Istimewa Yogyakarta: Perspektif Kerjasama Antar Daerah dan Peran Kelembagaan - Hurairah Haqi Ikhlasi; M Sandy Firdaus (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2025)
Waste management in the Special Region of Yogyakarta (DIY) faces substantial challenges due to rapid population growth and urbanization, which have led to a surge in waste volume exceeding the available management capacity. This study aims to identify key issues in DIY's waste management from the perspectives of inter-regional cooperation and institutional roles. A gap analysis method was applied to compare field conditions with existing regulatory frameworks. The findings reveal that despite the presence of various policies and legal instruments related to waste management, implementation remains suboptimal. This is primarily due to weak coordination among districts, the absence of an integrated inter-regional waste management institution, and low public participation in waste reduction and separation efforts. Furthermore, the application of modern waste processing technologies is still limited, constrained by resource and investment limitations. This study recommends strengthening regional institutions, enhancing cooperation among local governments, increasing public involvement, and adopting innovative waste treatment technologies. A more integrated and collaborative approach is expected to improve the effectiveness and sustainability of waste management practices in DIY.